(untitled) (Revista de Investigaciones Universidad del Quindío, 2013)
Reaction of YCl3 with Li[N(SiMe3)2] in a mixture toluene-tetrahydrofurane gives the complex YCl2[N(SiMe3)2] (THF)3 (1). This complex reacts with the tridentate ligands 2,6-bis(3,5-dimethylpyrazol-1-ylmethyl)pyridine and 2,6-bis(indazol-2-ylmethyl)pyridine to yield pincer complexes of general formula YCl2[N(SiMe3)2] 2,6-bis(azolylmethyl)pyridine-N,N,N(2,3). The yttrium(III) complexes were synthesized at NMR scale and characterized by NMR spectroscopy (1H, 13C, 29Si). The complexes behave as highly active catalysts in the polymerization of ε-caprolactone at room temperature. The polymers were characterized by means of IR and NMR spectroscopy, and SEC (Size Exclusion Chromatography).